Peran Guru dalam Membangun Keterampilan Sosial Emosional Anak Usia 5-6 Tahun di TK Islam Terpadu Nurul Ilmi - Septi Ayu Harahap; Rustam Pakpahan; Ahmad Syukri Sitorus (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Socio-emotional skills are an essential aspect that must be developed from an early age because they directly influence children’s ability to interact, regulate emotions, understand themselves, and adapt to their environment. The age of 5–6 years is a very strategic period for instilling these skills, as at this stage children begin to learn how to express feelings, build relationships with peers, and understand prevailing social norms. Therefore, early childhood education should not only focus on cognitive development, but also on character formation and strengthening socio-emotional skills. This study aims to describe in depth the role of teachers in developing socio-emotional skills of children aged 5–6 years at TK Islam Terpadu Nurul Ilmi. The research employed a qualitative approach with a descriptive method. Data were collected through classroom observations of children’s activities, in-depth interviews with teachers, and documentation of learning processes. The data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. The findings revealed that the socio-emotional skills of children at TK Islam Terpadu Nurul Ilmi were categorized as good, covering aspects of self-awareness, emotional regulation, prosocial behavior, cooperation, and responsibility. Teachers played a central role through their functions as educators, motivators, communicators, and supervisors. The strategies used included habituation of positive behavior, role modeling, warm communication, and monitoring children’s social interactions. This study emphasizes the importance of integrating socio-emotional development into daily learning activities, as well as the need for collaboration between teachers and parents to create consistent parenting patterns at home and school. The implications of this research are expected to serve as input for early childhood teachers in designing learning strategies that holistically support children’s growth and development.